Peningkatan Kemampuan Guru SDN 5 Gedong Tataan dalam Memanfaatkan Lingkungan Sekolah sebagai Sumber Belajar melalui Diskusi Kelompok Kerja Guru (KKG) Tahun 2019 - Heriningsih, Heriningsih (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2022)
This research was conducted to improve teachers' ability to utilize the environment as a learning resource. The research was conducted at KKG Region II, Gedong Tataan District. The research subjects were 9 teachers at SDN 5 Gedong Tataan. The aim was to see an increase in the cognitive abilities and activities of SDN 5 Gedong Tataan teachers in their KKG activities. This study uses a reflective action research design carried out in 3 cycles. The results of data analysis for each cycle show that discussion activities in the KKG can improve cognitive abilities and increase the activity of teachers at SDN 5 Gedong Tataan, Gedong Tataan District, Pesawaran Regency.